Acute neuromuscular respiratory failure: a population-based study of aetiology and outcome in Northern Ireland. Issue 1062 (17th February 2014) - Carr, A S; Hoeritzauer, A I; Kee, R; Kinney, M; Campbell, J; Hutchinson, A; McDonnell, G V
Abstract: Background: Acute neuromuscular respiratory failure (NMRF) is a life-threatening feature of a variety of neurological conditions that can present in extremis prior to the establishment of a definitive diagnosis, so early clinical decision making is difficult. Population-based data on the frequency, outcome and aetiological spectrum are lacking. Objective: To establish accurate epidemiological descriptive statistics in this patient group. Methods: The regional Intensive Care National Audit and Research Centre (ICNARC) database was searched for patients admitted with acute NMRF from 1/1/2000 to 31/12/2010. Demographics, diagnosis, length of intensive care unit (ICU) stay, follow-up and outcome (modified Rankin score (mRS)) were recorded. A comparison dataset of all non-NMRF neurology patients admitted to ICU was obtained. Results: 55 patients were identified; age 17–88 (median 66 years), M:F ratio 1:1.5, incidence rate (IR) 2.81 (2.12 to 3.66) cases per million person-years and mortality rate (MR) 0.26 (0.08 to 0.60) deaths per million person-years. Causes included inflammatory neuropathy (65%), myasthenia gravis (18%), rhabdomyolysis (2%) and amyotrophic lateral sclerosis (9%), and 5% were undiagnosed. Follow-up ranged from 0 to 7 years (median 500.5 days); long-term mRS 1 (range 0–6). NMRF patients were older (p<0.0001), had longer ICU stay (p<0.0001), but significantly better outcome (p<0.0001) than 93 non-NMRF neurology patients requiring ICU admission. Conclusion: Inflammatory and degenerative neuromuscular conditions can present in acute NMRF. Long-term outcome is good and MR is low, and significantly better than in other neurology patients requiring ICU admission despite longer ICU stay.